THE APPLICATION OF STUDENTS TEAM ACHIEVEMENT DIVISION TECHNIQUE TO IMPROVE STUDENTS' READING SKILL IN NARRATIVE TEXT - Kadir, Siska; Miolo, Sartin; Malabar, Fahria (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
This study aims to determine whether the application of the Student Team Achievement Division (STAD) technique can improve students' reading skills in narrative texts. The study sampled 30 students from class IX-4 of SMPN 4 Gorontalo. To collect data, a multiple-choice test was used adapted from various fairy tale stories, including